Referenciação e retextualização no ensino de língua portuguesa - Felício, Heloisa (2009)
In this research work, we have as theme the Referencing and our intention is to verify how occurs the process of introduction and resumption / maintenance of referencing textual in rewritten texts produced by students at the Middle School of a public school in the city of Mogi Guaçu, São Paulo state. The research is in Linguistics Textual field and it is justified by the significance of this theme, mostly by the context of the education for text production by Portuguese Language that values discursive and pragmatic dimension of written language. Thinking about the objective of the research, we selected a corpus composed by five rewritten stories of Machado de Assis tale called The wallet , and we compared how the referencing is introduced and maintained in the rewritten and the original story. The results show that in the rewritten stories, after introduced the referencing, the students maintained it mostly using the repetition of this referencing, or using pronouns, ellipse, and defined nominal expressions in order to guarantee the referencing progression and the text cohesion. Either in the original text or in the rewritten ones, the results point that the referencing are introduced mostly by names or by defined and undefined nominal expressions. Saying about the resumption and maintenance, the author of the original text uses the pronouns, the referencing repetitions, the ellipse, defined and undefined nominal expressions and indirect anaphora